2001
DOI: 10.1002/pros.1096
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H1 receptor activation inhibits the proliferation of human prostatic adenocarcinoma DU‐145 cells

Abstract: Histamine inhibits the proliferation of DU-145 cells through the activation of H(1) receptors coupled to phosphoinositide hydrolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Similarly, loss of SLC18A2 might sensitize prostate cancer cell to the promigratory effects of norepinephrine released from sympathetic nerves (17,18) and/or antiapoptotic stimuli from circulating epinephrine (19), both mediated via h 2 -adrenergic receptors. Histamine, secreted by infiltrating mast cells, augments h 2 -adrenergic receptormediated responses in prostate cancer cells in vitro independent of the H1 receptor (44) but has also been shown to inhibit proliferation via the H1 receptor (16). Finally, perineural invasion is regarded as a key mechanism for prostate cancer spreading, where neurons in the prostate seem to be a source for tumor-promoting paracrine factors, leading to reduced apoptosis and increased proliferation of nearby prostate cancer cells (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, loss of SLC18A2 might sensitize prostate cancer cell to the promigratory effects of norepinephrine released from sympathetic nerves (17,18) and/or antiapoptotic stimuli from circulating epinephrine (19), both mediated via h 2 -adrenergic receptors. Histamine, secreted by infiltrating mast cells, augments h 2 -adrenergic receptormediated responses in prostate cancer cells in vitro independent of the H1 receptor (44) but has also been shown to inhibit proliferation via the H1 receptor (16). Finally, perineural invasion is regarded as a key mechanism for prostate cancer spreading, where neurons in the prostate seem to be a source for tumor-promoting paracrine factors, leading to reduced apoptosis and increased proliferation of nearby prostate cancer cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…Although murine knockout models have disclosed important biological roles of SLC18A2 in the nervous system (10 -12), its possible function in normal and malignant prostate biology remains unknown. However, several of the monoamines that are substrates for SLC18A2-mediated transport have been shown to influence growth (13 -15), proliferation (16), migration (17,18), or apoptosis (19) of prostate cancer cells in vitro and in vivo.…”
mentioning
confidence: 99%
“…Recently, it has been suggested that mast cells influence the proliferation of cancer cells and promote the invasion of cancer cells by reorganizing the cancer cell's microenvironment and modulating immune responses to cancer cells. Mast cells induce the migration of T-cells and antigen-presenting dendritic cells and subsequently may affect cancer cell functions [152]. In addition, other cells such as eosinophilic granulocytes, dentritic cells, and T-cells may also contribute to cancer cell stimulation that induces the onset of invasiveness and epigenetic alterations for a certain type of cancer cells [152,154].…”
Section: Effect Of Adjacent Cells (Non-endothelial Cells) On Cancer Cmentioning
confidence: 99%
“…Previously, it has been reported that histamine released by mast cells upon stimulation, increases the stiffness of histamine receptor presenting cells such as endothelial cells [147]. Thus, several cancer cells types possess also histamine receptors [148][149][150][151] and might be stimulated by mast cells that are frequently found in the neighborhood of tumor masses [152,153]. Until now, the function of mast cells within these tumors or in their close neighborhood remains to be unclear.…”
Section: Effect Of Adjacent Cells (Non-endothelial Cells) On Cancer Cmentioning
confidence: 99%
“…Furthermore, elevated expression of the HRH1 gene has been shown to be associated with poor survival for both lung cancer and B-cell lymphoma patients (70). Several other studies demonstrated that H1R activation suppressed cell proliferation in prostate cancer (67), melanoma (40), and leukemia (31) cells and promoted cell migration of cervical carcinoma cells (57). Altogether, the effects of histamine-receptor activation seem to be tissue specific, depending on relative distributions of histamine receptors in different tissue types (37).…”
Section: Introductionmentioning
confidence: 99%